Firm entry, excess capacity and aggregate productivity - Anthony Savagar; Huw Dixon (Cardiff University, Cardiff Business School, 2017)
Slow firm entry over the business cycle causes measured TFP to vary endogenously because incumbent firms bear shocks. Our main theorem states that imperfect competition and dynamic firm entry are necessary and sufficient conditions for these endogenous productivity fluctuations. The result focuses on the short-run absence of entry and incumbents' output response given this quasi-fixity. Quantitatively we show the endogenous productivity effect is as large as a traditional capital utilization effect.
Keywords: E32; D21; D43; L13; C62; 330; dynamic entry; endogenous productivity; endogenous sunk costs; business stealing; business cycle; continuous time